The Effectiveness of Comic Assisted Problem Based Learning Model on Numeracy Literacy Skills of Eighth Grade Students - Ichda Aulia Farda; Aprilia Nurul Chasanah; Syita Fatih 'Adna (Jurnal Pendidikan Matematika)
Based on the initial test, the students' numeracy literacy ability is still relatively low. A learning model and media are needed that can familiarize students to solve problems in everyday contexts. The study aims to analyze the completeness of the numeracy literacy ability of students who are given the comic-assisted PBL learning model and students who are given the direct learning model, as well as analyze the effectiveness of the comic-assisted Problem Based Learning model on the numeracy literacy ability of grade VIII students. The research method is quantitative research with a nonequivalent posttest control group design. The sample in this study is two classes, namely as a control class and an experimental class. The data collection technique uses tests, interviews, observations, and questionnaires. The data analysis techniques used are z-test analysis and independent sample t-test. The results of the posttest of numeracy literacy skills in the experimental class and the control class were obtained tvalue = 2,95 > ttabel = 1,68 which shows that H0 rejected and H1 accepted. Conclusion of  this study shows that the comic-assisted Problem Based Learning model is more effective on numeracy literacy skills compared to the direct learning model.